Positive Solutions for a Fractional Boundary Value Problem with a Perturbation Term. (7th August 2018) - Zou, Yumei
Abstract : We obtain some new upper and lower estimates for the Green's function associated with a fractional boundary value problem with a perturbation term. Criteria for the existence of positive solutions of the problem are then obtained based on it.